2000
DOI: 10.1093/ajcn/71.2.550
|View full text |Cite
|
Sign up to set email alerts
|

Severe linear growth retardation in rural Zambian children: the influence of biological variables

Abstract: Unlike other studies, we did not identify specific biological factors, such as health and micronutrient status, which contribute to the retardation of linear growth. The normal zinc and iodine statuses of the children suggest that at least these factors are not causal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
3
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 25 publications
5
33
3
6
Order By: Relevance
“…Although other studies have reported that children residing in rural areas have a substantially higher risk of poor nutritional status compared to their urban counterparts (Hautvast et al, 2000;Fox and Heaton, 2012), our study did not show evidence of such associations. The primary reason for this finding was that the current study was conducted within a predominantly rural context.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although other studies have reported that children residing in rural areas have a substantially higher risk of poor nutritional status compared to their urban counterparts (Hautvast et al, 2000;Fox and Heaton, 2012), our study did not show evidence of such associations. The primary reason for this finding was that the current study was conducted within a predominantly rural context.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar patterns have been reported in earlier studies which have recorded a dramatic rise in the prevalence of stunting with age among African children (Stoltzfus et al, 1997;Hautvast et al, 2000;Senbanjo et al, 2011). Stoltzfus et al (1997) as well as Glewwe and Jacoby (1995) have postulated that, parents probably enrol the more healthy children in school at earlier ages.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Recumbent length (children less than two years old) or standing height (children Ն2 years old) was measured to the nearest 0.1 cm using wooden measuring boards with a sliding foot or head piece. 17 The Z-scores for height-for-age (HAZ), weight-for-age (WAZ), and weight-for-height (WHZ) were calculated using reference data from the U.S.-based National Centers for Health Statistics (NCHS) and the World Health Organization 18 in EPI-Info version 6 (Centers for Disease Control and Prevention, Atlanta, GA). Children were classified as stunted, underweight, or wasted if their HAZ, WAZ, or WHZ was <−2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Children of those mothers, who have poor health as expressed by low body mass index, are more likely to be nutritionally poor. Studies suggest that under-nutrition is often inter-generational in nature that affects the health of the mother and the child throughout their life cycle [49,50]. …”
Section: Discussion Of Findingsmentioning
confidence: 99%